Analisis Efektivitas Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Penerimaan dan Pengeluaran Kas (Studi Pada Koperasi Kementerian Agama Kota Medan) - Khairil Fitrah Harahap; Hendra Harmain; Wahyu Syarvina (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effectiveness of the Accounting Information System and Internal Control of Cash Receipts and Expenditures in the Cooperative of the Ministry of Religious Affairs of Medan City. The method used in this study is qualitative with descriptive analysis, with data collection techniques through interviews and documentation. The result of this study is that the application of the Accounting Information System on cash receipts and expenditures has been effective and efficient because the parts of the functions in the Cooperative of the Ministry of Religious Affairs of Medan City, one of which is the cash function. The cash function is responsible for the cash flow statement process. In the cash function has been recorded well through software called Smartcoop. This software is very helpful for employees in processing data so that it can present information that is quite clear. The implementation of the Internal Control System in the Medan Regional Office on cash receipts and expenditures at the Cooperative of the Ministry of Religious Affairs of Medan City has been running effectively. There is a separation of functions, namely the cash function and the accounting function where there is no limitation of duties or positions carried out in the process of receiving and disbursing cash.